A jornada de luta de “mujeres libres”; uma análise sobre o papel da revista na revolução e guerra civil espanhola - Silva, Talita Sobrinho da (2020)
The aim of this work was to analyze the editorials of the magazine Mujeres Libres, during the years 1936 to 1937 in Spain. You editors analyzed had the Spanish Revolution and Civil War as methodological and historical feature. Either the objective of the work was to locate the pages of the magazines or the positions constructed by Mujeres Libres during the years of conflict. A research methodology consists of readings and analyzes by two publishers and a selection of materials that demonstrate the role of Mujeres Libres. Since the magazine was fundamental for the political and professional training of women during the Spanish revolution, always having the female labor force as a political and organizational objective. The editorial of Mujeres Libres was organized as follows: the content covered always referred to women, work, the Revolution and the Spanish Civil War. The magazine contained layers, diagrams and illustrations. In all, 13 issues were published between the first of May 1936 and the last, not before 1938. Keywords: Spanish Civil War- Mujeres Libres- Anarchism-Magazine.